(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective To describe the knowledge and practices of nutritional care for young children among mothers in two border communes of Thanh Hoa province in 2025. Methods A cross-sectional descriptive study was conducted on 200 mothers caring for children under 24 months of age in Na Meo Commune (Quan Sơn District) and Pu Nhi Commune (Muong Lat District), Thanh Hoa Province, from April to October 2025. Data were collected using a pre-structured questionnaire regarding knowledge and practices of young child nutrition care. Data analysis was performed using STATA version 12.0 software, employing descriptive statistics and the chi-squared χ² test. Results The Mong and Thai ethnic groups accounted for 42.5% and 44.0% of the study participants, respectively. Only 53.5% of mothers knew that breast milk is the best first food for infants; 29.0% correctly understood exclusive breastfeeding during the first 6 months; and 27.5% knew that children should be breastfed up to 24 months of age. The rate of mothers knowing that children need to be breastfed within the first hour after birth was 28.0%. Only 13.0% of caregivers knew that children need a diverse diet of food groups during complementary feeding. The rate of mothers exclusively breastfeeding for the first 6 months reached 29.0%, and initiating breastfeeding within the first hour after birth reached 28.0%. Additionally, 54.5% of mothers attended antenatal care 3 or more times, and 59.5% used iron or multiple micronutrient supplements during pregnancy. Conclusions Knowledge and practices regarding nutritional care for young children among mothers in the border areas of Thanh Hoa remain limited, particularly regarding breastfeeding and appropriate complementary feeding. It is essential to strengthen nutritional education and communication tailored to the cultural and linguistic characteristics of these ethnic minorities.